Glosa do wyroku Sądu Najwyższego z dnia 23 listopada 2016 roku, III KK 225/16 - Mariusz Nawrocki (Acta Iuris Stetinensis, 2017)
Gloss refers to the problem of continuous crime and the implications of it in criminal law. It touched on the issue of the essence of a continuous crime, the definition of its temporal framework, the meaning of the construction of the unity of the crime, and, therefore, the issue of the beginning of the period of prescription of a continuous crime.